The Dynamics of Moonlighting in Pakistan (The Pakistan Development Review, 2009)
The study explores the dynamics of moonlighting, demographics, human capital and association of occupations between primary and secondary job. The paper is based on cross-section data Labour Force Survey 2006-07 and limited to male wage workers residing in urban areas. Among two motives according to theoretical framework of moonlighting; first, constraint on hours worked in first job and second is wage rate is lower than the reservation wage in the primary occupation; within limited information available on different variables our results are skewed toward first motive and earnings from the primary occupation are insignificant in moonlighting decision. The model specification also attempts to correct the endogenous regressor in probit estimation. Among moonlighters ‘Professionals’ and ‘Technicians’ are holding their secondary job in same occupational category; apart from these two occupational categories managers and elementary occupations also seems popular for moonlighting. JEL classification: J22, J24 Keywords: Moonlighting, Labour Mobility, Occupational Association